Biocontrol potential of Pseudomonas rhodesiae GC-7 against the root-knot nematode Meloidogyne graminicola through both antagonistic effects and induced plant resistance - Ye, Shan; Yan, Rui; Li, Xinwen; Lin, Yufeng; Yang, Zhuhong; Ma, Yihang; Ding, Zhong (Frontiers in Microbiology, 2022)
Plant-parasitic nematodes (PPNs) cause serious damage to agricultural production worldwide. Currently, because of a lack of effective and environmental-friendly chemical nematicides, the use of microbial nematicides has been proposed as an eco-friendly management strategy to control PPNs. A nematicidal bacterium GC-7 was originally isolated from the rice rhizosphere, and was identified as Pseudomonas rhodesiae. Treatment with the fermentation supernatant of GC-7 in vitro showed a highly lethal effect on second-stage juveniles of Meloidogyne graminicola, with the mortality rate increasing to 95.82% at 24 h and egg hatching significantly inhibited, with a hatch inhibition rate of 60.65% at 96 h. The bacterium significantly reduced the level of damage caused by M. graminicola infestations to rice (Oryza sativa) in greenhouse and field experiments. Under greenhouse conditions, the GC-7 culture efficiently reduced the gall index and nematode population in rice roots and soils, as well as inhibited nematode development compared to the control. Under field conditions, application of the GC-7 consistently showed a high biocontrol efficacy against M. graminicola (with a control efficiency of 58.85%) and promoted plant growth. In addition, the inoculation of GC-7 in M. graminicola-infested rice plant fields significantly suppressed final nematode populations in soil under natural conditions. Furthermore, activities of plant defense-related enzymes, peroxidase, polyphenol oxidase, and phenylalanine ammonia-lyase were remarkably increased in plant roots treated with GC-7 compared with roots that were challenge to M. graminicola. Moreover, quantitative real-time PCR analysis showed that GC-7 significantly enhanced the expression of defense genes (PR1a, WRKY45, JaMYB, AOS2, ERF1, and ACS1) related to salicylic acid, jasmonic acid, and ethylene signaling pathways in rice roots after inoculation with GC-7 at different levels. The results indicated that GC-7 could be an effective biological component in the integrated management of M. graminicola infecting rice.